2005
DOI: 10.1055/s-2005-837521
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Insulin Aspart Compared to Biphasic Human Insulin Reduces Postprandial Hyperlipidemia in Patients with Type 2 Diabetes

Abstract: Compared to conventional human premixed insulin the prandial therapy with biphasic insulin aspart results not only in an improvement of glucose tolerance but also in a significant reduction of postprandial hyperlipemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…55 A number of studies have assessed HbA1c levels in patients treated with premixed human insulins versus those treated with premixed insulin analogs, including premixed insulin lispro formulations [57][58][59] and insulin aspart formulations. [60][61][62] While one study showed small but significant improvements in HbA1c levels after treatment with 50/50 premixed insulin lispro relative to premixed human insulins, 57 other studies failed to find similar advantages favoring premixed insulin analogs. 58,60,62 Consistently, however, patients receiving premixed insulin analogs exhibited improved PPG control relative to premixed human insulins, reflecting the higher absorption rate of the analogs.…”
Section: Clinical Effects Of Insulin Analogs Hba1cmentioning
confidence: 99%
See 1 more Smart Citation
“…55 A number of studies have assessed HbA1c levels in patients treated with premixed human insulins versus those treated with premixed insulin analogs, including premixed insulin lispro formulations [57][58][59] and insulin aspart formulations. [60][61][62] While one study showed small but significant improvements in HbA1c levels after treatment with 50/50 premixed insulin lispro relative to premixed human insulins, 57 other studies failed to find similar advantages favoring premixed insulin analogs. 58,60,62 Consistently, however, patients receiving premixed insulin analogs exhibited improved PPG control relative to premixed human insulins, reflecting the higher absorption rate of the analogs.…”
Section: Clinical Effects Of Insulin Analogs Hba1cmentioning
confidence: 99%
“…58,60,62 Consistently, however, patients receiving premixed insulin analogs exhibited improved PPG control relative to premixed human insulins, reflecting the higher absorption rate of the analogs. [58][59][60][61][62] …”
Section: Clinical Effects Of Insulin Analogs Hba1cmentioning
confidence: 99%
“…However, there is more and more evidence that postprandial hyperglycemia is a risk factor in its own right. Endothelial dysfunction can be reversed by correction of postprandial glucose excursion by acarbose specifically controlling postprandial glucose excursion and rapid-acting insulin analogues [23]. Several studies have reported that acute hyperglycemia reduces the release of NO [23] probably mediated by free radicals [18].…”
Section: Effects On Endothelial Function and Vascular Wallmentioning
confidence: 99%
“…Endothelial dysfunction can be reversed by correction of postprandial glucose excursion by acarbose specifically controlling postprandial glucose excursion and rapid-acting insulin analogues [23]. Several studies have reported that acute hyperglycemia reduces the release of NO [23] probably mediated by free radicals [18]. Glucose intolerance was also associated with abnormalities in the fibrinolytic system [24].…”
Section: Effects On Endothelial Function and Vascular Wallmentioning
confidence: 99%
“…Randomized controlled trials have demonstrated the safety and efficacy of BIAsp 30 compared with other insulins (including insulin glargine, human insulin, biphasic insulin lispro, and premixed human insulin) [6][7][8][9][10] . Moreover, observational studies have confirmed and extended such findings and yielded safety and efficacy information in 'real world' patient groups which are more clinically and racially diverse 11,12 .…”
Section: Introductionmentioning
confidence: 99%